A novel block of plant virus movement genes. (15th July 2016) - Lazareva, Ekaterina A.; Lezzhov, Alexander A.; Komarova, Tatiana V.; Morozov, Sergey Y.; Heinlein, Manfred; Solovyev, Andrey G.
Summary: Hibiscus green spot virus (HGSV) is a recently discovered and so far poorly characterized bacilliform plant virus with a positive‐stranded RNA genome consisting of three RNA species. Here, we demonstrate that the proteins encoded by the ORF2 and ORF3 in HGSV RNA2 are necessary and sufficient to mediate cell‐to‐cell movement of transport‐deficient Potato virus X in Nicotiana benthamiana . These two genes represent a specialized transport module called a 'binary movement block' (BMB), and ORF2 and ORF3 are termed BMB1 and BMB2 genes. In agroinfiltrated epidermal cells of N. benthamiana, green fluorescent protein (GFP)‐BMB1 fusion protein was distributed diffusely in the cytoplasm and the nucleus. However, in the presence of BMB2, GFP‐BMB1 was directed to cell wall‐adjacent elongated bodies at the cell periphery, to cell wall‐embedded punctate structures co‐localizing with callose deposits at plasmodesmata, and to cells adjacent to the initially transformed cell. Thus, BMB2 can mediate the transport of BMB1 to and through plasmodesmata. In general, our observations support the idea that cell‐to‐cell trafficking of movement proteins involves an initial delivery to membrane compartments adjacent to plasmodesmata, subsequent entry of the plasmodesmata cavity and, finally, transport to adjacent cells. This process, as an alternative to tubule‐based transport, has most likely evolved independently in triple gene block (TGB), double gene block (DGB), BMB and the single gene‐coded transport system.